Analisis pemakaian deiksis pada novel yang berjudul “12 Cerita Glen Anggara” Karya Luluk HF serta implikasinya terhadap pembelajaran Novel - Astry Meiranti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to determine the use of deixis in the novel entitled "12 Stories of Glen Anggara" by Luluk HF and its implications for novel learning. This research focuses on looking for elements of persona deixis, time deixis, space or place deixis, and social deixis in the novel "12 stories of Glen Anggara". The main problem of this research is to look for the use of deixis in the content of the novel entitled "12 stories of Glen Anggara" in detail in pragmatic studies. The researcher also aims to have implications for the results of deictic analysis in the novel "12 Stories of Glen Anggara" in learning novels in high school. This research is descriptive research using a qualitative approach with the type of research used is content analysis techniques. The results of this research found that many deictic elements were used in the novel "12 Stories Glen Anggra" by Luluk HF. The tendency for the deictic elements contained in this novel is persona deixis because the novel writer tends to bring up characterization elements followed by time deixis, indicating deixis, place deixis, and social deixis.